ANALISIS INTERDEPENDENSI KOMPLEKS PADA KERJA SAMA SEKTOR ENERGI CHINA-RUSIA DALAM SHANGHAI COOPERATION ORGANIZATION (SCO) - Dickdemas Asaddin, (2023)
Since Cold War period, China and Russia have been two major powers collaborating to achieve their political goals in the context of international relations. Furthermore, they are are interdependent, particularly in the energy sector, as evidenced by their energy trade activities. Moreover, China plays an active role in promoting regional cooperation through the Shanghai Cooperation Organization (SCO), indicating a strong level of interdependence between the two countries. The presence of interdependence within SCO framework is influenced by issues arising from each country. The expansion of cooperation within the SCO framework to energy cooperation has created a more complex pattern of collaboration than what is apparent at first glance. Other than the military aspects, economic, political, and other related roles also play a crucial part in this relationship. Therefore, this topic allows for broader and critical analysis, particularly in energy cooperation context. Energy sector serves as a vital element that strengthens their mutual dependency. China is the world's largest energy consumer, while Russia possesses abundant energy resources. Cooperation in this sector brings mutual benefits. They rely on each other in terms of energy, establishing strong relationship that mutually influences their energy policies and economic interests. However, it's important to take holistic view, considering other factors that affect this energy cooperation. Apart from economic cooperation, there are also political aspects and other relevant factors that need to be taken into account. Both countries have their own interests and differing perspectives on certain global issues, such as foreign policies and specific regional matters.